Mutational analysis of highly conserved residues in the phage phiC31 integrase reveals key amino acids necessary for the DNA recombination. - Shaohui Liu; Jinfang Ma; Wei Wang; Maoxiang Zhang; Qingting Xin; Siman Peng; Rongxiu Li; Huanzhang Zhu (PLoS ONE, 2010)
BACKGROUND: Amino acid sequence alignment of phage phiC31 integrase with the serine recombinases family revealed highly conserved regions outside the catalytic domain. Until now, no system mutational or biochemical studies have been carried out to assess the roles of these conserved residues in the recombination of phiC31 integrase. METHODOLOGY/PRINCIPAL FINDINGS: To determine the functional roles of these conserved residues, a series of conserved residues were targeted by site-directed mutagenesis. Out of the 17 mutants, 11 mutants showed impaired or no recombination ability, as analyzed by recombination assay both in vivo and in vitro. Results of DNA binding activity assays showed that mutants (R18A, I141A, L143A,E153A, I432A and V571A) exhibited a great decrease in DNA binding affinity, and mutants (G182A/F183A, C374A, C376A/G377A, Y393A and V566A) had completely lost their ability to bind to the specific target DNA attB as compared with wild-type protein. Further analysis of mutants (R18A, I141A, L143A and E153A) synapse and cleavage showed that these mutants were blocked in recombination at the stage of strand cleavage. CONCLUSIONS/SIGNIFICANCE: This data reveals that some of the highly conserved residues both in the N-terminus and C-terminus region of phiC31 integrase, play vital roles in the substrate binding and cleavage. The cysteine-rich motif and the C-tail val-rich region of phiC31 integrase may represent the major DNA binding domains of phiC31 integrase.